Directions of Civil Service Institutional Transformation - G. A. Borshevskiy (Управление)
The concepts of rational bureaucracy, New Public Management and Good Governance were studied. It is indicated that wrongly assume that one of them is more progressive, because all concepts originally aimed at the rationalization of the public service and subordination its own interests according the interests of society. A set of conditions for the participation of citizens in governance exists today. There are a networked organization, a partnership, a production of public goods, and value of public interest. It is proved that in the Concept of the Russian Federation civil service reform (2001) laid the modernization potential for building an open and democratic public service. We postulate the classification of the barriers and challenges that hinder the civil service reform, and we formulate the growth points and the alternative transformation vectors. Then we consider the risks of each alternative in the short, medium and long term, and how to overcome them. It is indicated that the priority should be the harmonization of the legal framework for civil service and public sector. In the first step is need the convergence of the legal content of civil service with other activities in the public sector, and the renouncement the civil servants to serve to politicians, which is aimed at increasing their personal responsibility. It is necessary to implement the new basic legal principle of targeting efforts of the civil servants to achieve economic growth and improve the quality of citizens life. In the next step a new phenomenon – the public service – should be formed. The new public service will include the civil service, municipal service and the public sector organizations, as well as some other types of organizations. This requires some changes in the personnel policy: the formation of a single personnel reserve for the entire public service, improving the qualification requirements for all public positions based on professional specializations, and ensuring the effective public control. A systematic approach to the creation of the public service will increase the efficiency of public institutions and their resilience in the face of global instability. Our conclusions were tested in draft the Strategy of socio-economic development of Russia for the period till 2030.